Community Perspectives on Redistributive Justice and Institutional Credibility in Remote Land Policy Implementation - Mohammad, Nur Laila Binti (Journal of Social Science Studies, 2023)
This literature-based inquiry examines how communities in remote areas interpret the success of land redistribution policies implemented in their regions. The review synthesizes research across rural sociology, land governance, and development studies to identify key dimensions that shape public perception. Findings indicate that community evaluations are rarely based on legal titling or formal program completion alone. Instead, beneficiaries assess redistributive success through criteria such as procedural transparency, land usability, long-term tenure security, cultural alignment, and symbolic acknowledgment. Local perceptions are also influenced by gender dynamics, political brokerage, infrastructure access, and historical memory, revealing that administrative redistribution often diverges from communal interpretations. In remote settings where legal pluralism, logistical constraints, and limited state presence prevail, land reforms are filtered through vernacular understandings of justice, legitimacy, and continuity. The review emphasizes that perception is both a diagnostic and generative force in land governance, affecting cooperation, compliance, and long-term viability. It concludes by calling for evaluation frameworks that prioritize social embeddedness, participatory engagement, and institutional responsiveness to local worldviews. By attending to how land redistribution is received and narrated at the community level, this study offers insights into improving both policy design and implementation in marginalized territories.